Characterizations of handwashing sink activities in a single hospital medical intensive care unit - Grabowski, M.; Lobo, J.M.; Gunnell, B.; Enfield, K.; Carpenter, R.; Barnes, L.; Mathers, A.J. (The Journal of hospital infection, 2018)
Handwashing sink drains are increasingly implicated as a potential reservoir of antibiotic-resistant bacteria in hospital outbreaks; however, usage patterns that may promote this source remain unknown. To understand behaviours in the intensive care unit (ICU) that may facilitate establishment and nosocomial transmission of multidrug-resistant Gram negatives from a sink-trap reservoir to a patient. Motion-sensitive cameras captured anonymized activity paired with periodic in-person observations during a quality investigation from four ICU sinks (two patient rooms and two patient bathrooms) in a university hospital. We analysed 4810 sink videos from 60 days in patient rooms (3625) and adjoining bathrooms (1185). There was a false-positive rate of 38% (1837 out of 4810) in which the camera triggered but no sink interaction occurred. Of the 2973 videos with analysed behaviours there were 5614 observed behaviours which were assessed as: 37.4% medical care, 29.2% additional behaviours, 17.0% hand hygiene, 7.2% patient nutrition, 5.0% environmental care, 4.2% non-medical care. Handwashing was only 4% (224 out of 5614) of total behaviours. Sub-analysis of 2748 of the later videos further categorized 56 activities where a variety of nutrients, which could promote microbial growth, were disposed of in the sink. Several non-hand hygiene activities took place regularly in ICU handwashing sinks; these may provide a mechanism for nosocomial transmission and promotion of bacterial growth in the drain. Redesigning hospital workflow and sink usage may be necessary as it becomes apparent that sink drains may be a reservoir for transmission of multidrug-resistant bacteria.